Application of Discovery Learning Model to Increase Student Activity in Civics Education Courses - Sitti Zamala; Mukhamad Murdiono; Puji Wulandari; Nasiwan Nasiwan (Riviera Publishing, 2025)
This research aimed to apply the Discovery Learning model as a means of improving student engagement and academic achievement within the Civic Education program. The study employed a Classroom Action Research (CAR) methodology, conducted over two cycles encompassing the stages of planning, implementation, observation, and reflection. The results revealed that the use of the Discovery Learning model significantly enhanced students’ active participation and learning outcomes. This was demonstrated by an 18% increase in average active participation, rising from 75% in the first cycle, categorized as moderately active, to 93% in the second cycle, which is considered highly active. Additionally, the implementation of Discovery Learning proved effective in boosting students’ academic performance in the Civic Education course, as indicated by a 19% improvement from 76% in the first cycle (fairly good) to 95% in the second cycle.